Connectivity from ipsilateral and contralateral dorsolateral prefrontal cortex to the active primary motor cortex during approaching-avoiding behavior. (December 2022) - Xia, Xue; Wang, Dandan; Wang, Linqi; Li, Xiangming; Chen, Robert; Liu, Yu; Zhang, Jian
Abstract: Automatic action tendency is reflected by a fast reaction to approach positive stimulus and to avoid negative stimulus (automatic behaviors), while a slow reaction to approach negative stimulus and avoid positive stimulus (controlled behaviors). The dorsolateral prefrontal cortex (DLPFC) is involved in the modulation of the automatic action tendency; however, it remains unclear whether DLPFC modulates the behavior through motor inhibition or excitation, as well as the exact timing of the modulation. We used paired-pulse, dual-site TMS protocols to investigate the connectivity between left/right DLPFC and the left primary motor cortex (M1) during the manikin task performed with the right hand. For the behavioral data, the results from reaction time (RT) and premotor time (PMT), which represents the beginning of finger movements, of the approaching-avoiding behavior in both experiments showed a shorter duration for automatic behavior compared to the controlled behavior. There was stronger facilitation of the left DLPFC-left M1 connectivity at interstimulus-interval of 25 ms in controlled behavior compared to automatic behavior (positive-approaching vs. positive-avoiding: P  = .002; negative-avoiding vs. negative-approaching: P  = .017). The right DLPFC-left M1 connectivity did not change with the task. The present study confirmed the automatic action tendency from both reaction time and the premotor time. During the right-handed task, the DLPFC contralateral but not ipsilateral to the effector could facilitate the left M1 to speed up the execution of the controlled behavior through a polysynaptic pathway.